PROGRAM NASIONAL UNTUK ELIMINASI FILARIASIS LIMFATIK: STUDI KASUS DI KABUPATEN PEKALONGAN, JAWA TENGAH - Anggi Septia Irawan; Hasan Boesri; Sidiq Setyo Nugroho (Balai Besar Penelitian dan Pengembangan Vektor dan Reservoir Penyakit (B2P2VRP) Salatiga, 2018)
Programmes to eliminate lymphatic filariasis are underway in all provinces of Indonesia. Central Java is big ten chronic case of Lymphatic Filariasis (LF) from 34 provinces in Indonesia. Started in 2015, Ministry of Health Republic Indonesia launched filariasis elimination by implementing preventive mass drug administration (MDA) or “POPM”. At least as 65% of the population in the district/city are given diethylcarbamazine citrate (DEC) and albendazole. This study aims to determine the constraints and problems encountered in the MDA implementation and the steps toward filariasis elimination. The method applied is a review of the scientific article, policy inventory, discussions with experts and practitioners, as well as field data confirmation. This study result describes of MDA coverage in Pekalongan Regency above of minimal coverage 65%, and around three years subsequently reaching 80%, the occurrence of side reactions after consuming drugs lower than 1% from all population target. This study noted that MDA implementation in Pekalongan District has fulfilled the target. However, program evaluation not only tablet distribution, but also data of compliance with taking medication. Conclusion of this study is that MDA must also be supported by vector control and completion through molecular examination as an assessment of mosquito capacity as a vector of lymphatic filariasis.